Statehood and governance: challenges in Latin America - Jörg Faust (Deutsches Institut für Entwicklungspolitik (DIE), 2007)
Although Latin America is the world's most democratic developing region and democratization has also caused an economic dividend, many Latin American democracies have a precarious basis of legitimacy. While most Latin American states are not as fragile nor as repressive as in some other regions, there are still serious political deficiencies in many of the subcontinent's societies. No-go areas in urban centres and remote rural areas, high-levels of corruption and soaring levels of criminal violence are the most prominent among these shortcomings.Such political deficiencies are highly dysfunctional for overcoming existing socio-economic development barriers. One of the main origins of existing political problems and governments' fragility is that most of Latin America's democracies have not succeeded in establishing stable and democratic party systems. The fragmentation of the intermediary structure between citizens and state has not only made coherent reforms increasingly difficult but also encouraged governments to engage in populist “dirigismo” and “decretismo”. Thus, the promotion of “good” governance should continue to be a focus of development assistance.
Keywords: 330